Indonesian Pluralism and Democracy Under Challenge: A Social Reflection - Herdi Sahrasad (JICSA : Journal of Islamic Civilization in Southeast Asian, 2016)
This article mainly concerned on the reflection of pluralism practice in the Indonesia context. Although, this issue is becoming a commitment for the government to implement it in the wider context of society, a number of challenges have been demonstrated in this research proving that pluralism is still a common problem in this country. The author illustrated a lot of cases in different areas which happened that threaten harmony and peace in the Indonesia life. This research discusses both pluralism and democracy as the two important entities which could not be separated. To some extent, most of the people here have not yet understood basically about significance and meaning of pluralism. So that the side effect of the misunderstanding, sociologically, sparks up social conflicts and issues of identity  in  the name of God, religion or other primordialism.